Relationships between parameters of gall-bladder motility and neuroendocrine-immune complex and metabolism in men with chronic cholecystitis and pyelonephritis - Marfiyan, Olena M; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Marfiyan Olena M, Zukow Walery. Relationships between parameters of gall-bladder motility and neuroendocrine-immune complex and metabolism in men with chronic cholecystitis and pyelonephritis. Journal of Education, Health and Sport. 2015;5(12):434-449. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35660 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A434-449 http://pbn.nauka.gov.pl/works/684422 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 15.12.2015. Accepted: 17.12.2015. RELATIONSHIPS BETWEEN PARAMETERS OF GALL-BLADDER MOTILITY AND NEUROENDOCRINE-IMMUNE COMPLEX AND METABOLISM IN MEN WITH CHRONIC CHOLECYSTITIS AND PYELONEPHRITIS Olena M Marfiyan1,2, Walery Zukow3 1JSC “Truskavets’kurort”, Truskavets’, Ukraine olenka80@meta.ua 2Department of Pediatry, OO Bohomolets’ National Medical University, Kyiv, Ukraine 3Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl SUMMARY Objective. Long known about cholecystokinetic and diuretic effects balneotherapy on spa Truskavets’. However known about modulation by bioactive water Naftussya neuroendocrine-immune complex Aim: clarification relationships between parameters of gall-bladder motility and neuroendocrine-immune complex as well as metabolism. Material and Methods. At 22 men with chronic cholecystitis combined with pyelonephritis we recorded basal and postprandial volume of gall-bladder (Echoscopy by “Radmir”), urinary excretion electrolytes and nitrogenous metabolites, EEG ("NeuroCom"), HRV ("CardioLab+HRV"), plasma level of cortisol, testosterone and triiodthyronine (ELISA), routine immune parameters. Results. Discovered 23 neural, metabolic and immune parameters, canonical correlation which with the parameters of gall-bladder motility is very strong. In particular, basal and early (in 5 min) postprandial volume determinated positively by HRV markers of vagal tone (pNN 50 , HF, LF, VLF), Bayevskiy’s activity regulatory systems index, α-rhythm laterality index, θ-rhythm deviation, circulating immune complexes, chloride and magnesium urina concentration and electrokinetic index buccal epithelium as marker of biological age, while negatively determinated by passport age as well as by α-rhythm frequency, oxaluria and body massa. Tardy (in 15 and 30 min) postprandial volume determinated negatively by θ-rhythm asymmetry, killing index by neutrophils Staphylococcus aureus, glomerular filtration, diurese, creatinineuria, phosphaturia, while positively by sodium urina concentration. Conclusion. Cholecystokinetic effect balneotherapy on spa Truskavets’ may be the result of modulation of neuroendocrine-immune complex. Keywords: gall-bladder motility, neuroendocrine-immune complex, metabolism, relationships.